Control of ball moss (Tillandsia recurvata L.) in fruit trees in the central region of Peru - Valverde-Rodríguez, Agustina; Alvarez-Benaute, Luisa; Jara-Claudio, Fleli; Illatopa-Espinoza, Dalila; Cornejo, Antonio; Gabino-Benancio, Edinson (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
In the current era, it is common to witness the massive proliferation of epiphytes, particularly the species Tillandsia recurvata L., commonly known as ball moss, which adhere in large quantities to fruit trees of various species, affecting fruit growing in the inter-Andean valleys of Peru. This species causes a gradual but constant deterioration of the trunks and branches of the fruit vegetation, causing its eventual death, therefore, the purpose of the present study was to evaluate the combination of sodium bicarbonate, copper sulfate, vinegar, and yeast in the control of Tillandsia recurvata L. A completely randomized block design was applied with 10 treatments and 5 repetitions. The following variables were evaluated: weight, moisture loss, and grade of epiphyte damage. The results determined that sodium bicarbonate significantly reduced the weight of T. recurvata, decreasing from 2.2 g to 0.26 g; regarding moisture loss, an increase was observed from 25.62 % to 91.65 %, as well as damage and mortality increased significantly with the vinegar + sodium bicarbonate treatment. In conclusion, treatments with sodium bicarbonate and vinegar + sodium bicarbonate caused the greatest damage and mortality in ball moss.